Integrated Solid Waste Management for the Circular Economy: Challenges and Opportunities for Nepal - Subedi, Monika; Pandey, Supreme; Khanal, Ashish (Journal of Multidisciplinary Research Advancements, 2023)
The article emphasizes the importance of implementing Integrated Solid Waste Management (ISWM) and circular economy principles for effective solid waste management, which prioritizes waste prevention, recycling, and environmentally sound disposal practices. The article provides an overview of how ISWM and circular economy principles have been successfully implemented in several countries worldwide and emphasizes the need for their adoption in Nepal, where proper solid waste management systems are often inadequate or non-existent. The article provides insights into the challenges and opportunities for Nepal in adopting such practices and recommends practical methods for improving waste management in the country. The researchers conducted a comprehensive search of the available literature on the topic of ISWM and circular economy in Nepal to draw conclusions and recommendations for the future direction of solid waste management in Nepal. Although, there is the formulation of new laws and policies related to solid waste management in Nepal, the country lacks active implementation of the laws by both governments and waste management companies.